Pengembangan Sistem Informasi Verifikasi Keaslian Hasil Test Swab di Dunia Penerbangan (Studi Kasus: Kantor Kesehatan Pelabuhan Kelas 1 Soekarno-Hatta) - Nur Aisyah Asriani; Fajar Pradana; Yuita Arum Sari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The Soekarno-Hatta Airport Class I Aviation Health Office (AHO) is a government institution tasked with validating COVID-19 negative test result (CNTR) documents, which is one of the prerequisites for boarding a flight. At one point, there have been forgeries made to such documents, which passed the manual and offline validation process done by AHO. To solve this problem, the writer try to devise an Information System for Verification of Swab Test Result Authenticity, which performs the validation automatically and online, so that flying can be safer from the risk of COVID-19 spread. The system was built by using the prototype development method, which consists of several stages, including data collection, requirements analysis, prototype building, prototype evaluation, system design, system implementation and system testing. Based on iterations done, there were 13 requirements identified from 2 actors, COVID-19 testing labs, AHO and system admin. Implementation was done using the javascript programming framework ReactJS and NodeJS. System testing was divided into four stages which consist of unit testing with 3 samples, integration testing to produce valid results, validation testing to obtain valid results from test cases, and non-functional testing in the form of usability testing using the System Usability Scale (SUS) method that obtained a point of 73,46 from 15 respondents.